The Research Agenda of Green Education in Enhancing Environmental Concern and Green Consumption - Ali Mursid; Daliana Fehabutar; Desi Wulandari; Hasan Nuurul Hidaayatullaah (Indonesia Approach Education, 2021)
This research aims to provide an analysis of arguments regarding environmental education and environmental concern in the future. Based on the importance of educating the public or society about environmental awareness, several research agendas are recommended for future research, namely 1) Psychological theory such as motivation, both intrinsic and extrinsic factors, can be adapted to clarify the motivation of students or the community in taking environmental education which has an impact on environmental behavior, 2) Sociological theory such as social identity theory will be interesting to explain the behavior of student or community related to green concern, 3) stimulant organism response theory, 4) Concerning green consumption, 5) Research topics on green education and green concern that adapt cultural theory will be interesting and be a comprehensive perspective.